Aktivitas Antioksidan Dan Nilai Gizi Dari Beberapa Jenis Beras Dan Millet Sebagai Bahan Pangan Fungsional Indonesia - Adriamin Azis; Munifatul Izzati; Sri Haryanti (Jurnal Akademika Biologi, 2015)
In recent time, there is a change in diet behavior of people. Food color is potential as antioxidant activity, such as rice and millet. These two type of grain are potentialy been used as functional food. This study is aimed to analyze antioxidant activity and nutrition content in several rice and millet. The antioxidant activity of Garcinia skin was used as control. The antioxidant activity was measured by DPPH method. This research was designed by descriptive quantitative. Parameters was measured including antioxidant activity, water content, ash, fiber, fat, and protein content. Resuls  from this study showed that red rice (Oryzanivara L.) has the highest antioxidant activity, as much as 95,05%. This antioxidant activity is 0.92% higher than Garcinia skin. The fiber content in red rice was also the highest, wich is 7,50%, wihie the protein content was 13,78%. The black rise, has content 13.58% of protein. Antooxidant activity of pearl millet (Pennisestumnglaucum) was 4.92%, and protein content as much as 13,57%. Panicummiliaceum has higher antioxidant activity (8,09%) and 11,21% of protein content. The fiber content of Pennisestumglaucumwas 9,33%, while Panicummiliaceumwas 5,75%.Keyword: Antioxidant, food, rice, millet